Increasing the Functioning Efficiency of the Working Warehouse of the “UVK Ukraine” Company Transport and Logistics Center - Victor Aulin; Andrii Hrynkiv; Oleg Lyashuk; Yuriy Vovk; Sergii Lysenko; Dmytro Holub; Taras Zamota; Andrii Pankov; Mariana Sokol; Vadym Ratynskyi; Olena Lavrentieva (Communications - Scientific letters of the University of Zilina, 2020)
Competition in the field of logistics and individual transport services requires the constant analysis of logistics chains and their individual links. Given analysis enables implementation of new approaches to logistics companies and networks trade marketing in the offtake of certain types of goods. Industrial and commercial enterprises have to expand their trade and economic relations with other regions with the aim to provide the necessary sales volumes in the domestic market of regions and to go beyond it. Integration of the country's economy and the free trade policy orientation greatly simplify the task of establishing the free trade and economic relations between producers and consumers. However, there is a question of how quickly and efficiently; with minimal logistics costs, the goods at the right region of the customer should be delivered.The experiment on a one-storey closed warehouse No 3 of Brovary "UVK Ukraine", where a process of the crossdocking warehousing, with subsorting from a warehouse, has been conducted. The warehouse mainly works on trading networks. The loading of the warehouse has been performed with the input flow intensity within (12.3 ... 23.56 (t/h)). During the experiment, the number gain of loading and unloading machines (Electrostacks Reath Track OMG NEOS LAT 3.0) a pcs in the process of unloading, loading and moving consignments, has been examined. In addition, the increasing number of workers employed in non-mechanized forms of work, such as receiving and stacking cargo in the reception area (moving the relevant consignments to designated areas of the reception area and its arrangement), which in total is an increase of 4 employees in the technological process of the warehouse operation, has been investigated during the experiment. The growing of labor and mechanized resources makes it possible to better organize the work of the warehouse, reduce total costs and increase cargo output flow. Conducting the process of warehouse work optimization on the formed technology and corresponding labor and mechanized resources caused an increase of its efficiency. It has been found that the optimal values of intensity of the incoming cargo flow will be 17.93 (t/h); the number of employees engaged in non-mechanized labor - 12 workers, and loading and unloading machines - 3 (pcs). Under such conditions, the warehouse functioning according to the desirability level will reach value 0.792. In this case, the cost value of warehouse work is 181.07 US$/h and cargo output flow intensity is 10.23 (t/h). Results of experimental studies have shown that implementation of the proposed method of increasing the efficiency of warehouse work, based on the company "UVK Ukraine" may, on average, achieve a total cost reduction of 17.2% and an increase in output flow by 34.6% and the input flow by 10.3%.